Etude par modélisation moléculaire des interactions dans le système super moléculaire hôte/invitée. - RABIEA BRIKI (My University, 2022)
This study presents a computational investigation of inclusion complex formation between Guanosin and β-cyclodextrin in vacuum. Geometry optimizations were performed by B3LYP /6-31G (d), B3LYP/6-31G(d,p), levels of theory.B3LYP /6-31G (d) calculations shows that B orientation is more stable than A one, for each orientation, Guanosin istotally encapsulated in to β-CD cavity. The theoretical analyzes carried out by NBO, B3LYP /6-31G (d) and B3LYP/6-31G(d,p), made it possible to predict and visualize hydrogen bonds explaining the stability of the two orientations. Charge transfer between host and guestis the most important factor stabilizing the inclusion complex Guanosin /β-CD. The computation of the electron transitions of the two models by the density functional theory (TD-DFT) at the theoretical level B3LYP / 6-311G (d, p) in the solvent allowed to detect three absorption bands in the UV / visible for both models and to find that a charge transfer has occurred between the host and the guest. ------------------------------------------------------------------------------------------- Cette étude présente une analyse computationnelle de formation de complexe d'inclusion entre la Guanosine et la β-cyclodextrine dans le vide. Les optimisations de géométrie ont été effectuées par les niveaux de théorie B3LYP /6-31G (d), B3LYP/6-31G (d, p).B3LYP /6-31G (d) montre que l'orientation B est plus stable que l’orientation A. Pour chaque orientation, la Guanosine est totalement encapsulé dans la cavité β-CD. Les analyses théoriques effectuée par NBO, B3LYP /6-31G (d)et B3LYP/6-31G (d, p)ont permis de prévoir et visualiser des liaisons de type hydrogène justifiant la stabilité des deux orientations. Le transfert de charge entre l'hôte et l'invité est le facteur le plus important stabilisant le complexe d'inclusion Guanosine /β-CD. Le calcul des transitions électronique des deux modèles par la théorie de la fonctionnelle de la densité (TD-DFT) au niveau théorique B3LYP/6-311G (d, p) dans l'eau a permis de détecter trois bandes d'absorption dans l'UV/visible pour les deux modèles et de constater qu'un transfert de charge s'est produit entre l'hôte et l'invité.